COMPARISON OF CORONALLY ADVANCED FLAP WITH AND WITHOUT CONNECTIVE TISSUE GRAFT IN MILLER CLASS I GINGIVAL RECESSION (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To compare the clinical outcomes of Coronally Advanced Flap (CAF) alone and Coronally Advanced Flap combined with Connective Tissue Graft (CAF+CTG) in the treatment of Miller Class I gingival recession defects. Methodology: A comparative clinical study was conducted in the Department of Periodontology. Forty patients presenting with Miller Class I gingival recession were equally allocated into two groups. Group A received Coronally Advanced Flap alone, while Group B received Coronally Advanced Flap combined with Connective Tissue Graft. Clinical parameters including recession depth (RD), recession width (RW), probing depth (PD), clinical attachment level (CAL), width of keratinized tissue (WKT), and percentage of root coverage were recorded at baseline and six months postoperatively. Data were analyzed using SPSS version 26.0. Statistical significance was set at p